Salivary gland proteome during adult development and after blood feeding of female Anopheles dissidens mosquitoes (Diptera: Culicidae) - Benjarat Phattanawiboon (2018)
© 2016 Phattanawiboon et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Understanding changes in mosquito salivary proteins during the time that sporozoite maturation occurs and after blood feeding may give information regarding the roles of salivary proteins during the malarial transmission. Anopheles dissidens (formerly Anopheles barbirostris species A1) is a potential vector of Plasmodium vivax in Thailand. In this study, analyses of the proteomic profiles of female An. dissidens salivary glands during adult development and after blood feeding were carried out using two-dimensional gel electrophoresis coupled with nano-liquid chromatography-mass spectrometry. Results showed at least 17 major salivary gland proteins present from day one to day 21 post emergence at 8 different time points sampled. Although there was variation observed, the patterns of protein expression could be placed into one of four groups. Fifteen protein spots showed significant depletion after blood feeding with the percentages of the amount of depletion ranging from 8.5% to 68.11%. The overall results identified various proteins, including a putative mucin-like protein, an antiplatelet protein, a long form D7 salivary protein, a putative gVAG protein precursor, a D7-related 3.2 protein, gSG7 salivary proteins, and a gSG6 protein. These results allow better understanding of the changes of the salivary proteins during the adult mosquito development. They also provide candidate proteins to investigate any possible link or not between sporozoite maturation, or survival of skin stage sporozoites, and salivary proteins.